A preliminary design of the manual breast pump: an ergonomics approach - Nurul Syazrin, Roslan (2009)
This study is to design the manual breast pump with an ergonomics approach. The problem statement of the study is to solve the musculoskeletal problems among mothers especially those who feed their babies using the manual breast pump. Meanwhile, the objectives for this study is to design a manual breast pump with an ergonomics approach using the Solidwork and to analyze the designed manual breast pump using the manual calculation. The methodology for this project used the survey instrument which is questionnaires and the software for the design stage. Result is the chapter where the analysis of the questionnaires that were distributed to the respondents. It is also included the analysis of the main part using the manual calculation. Lastly, it recovers the conclusion for the project. The study hopefully can help the future researcher in order to create and develop the new design for the manual breast pump.